A coupled thermo-hydrologic-mechanical (THM) model to study the impact of hydrate phase transition on reservoir damage. (1st February 2021) - Liu, Xiaoqiang; Qu, Zhanqing; Guo, Tiankui; Sun, Ying; Rabiei, Minou; Liao, Hualin
Abstract: Thermal fluid injection is proven to be one of the effective methods to dissociate hydrate. The injection of thermal fluid can destroy the hydrate phase equilibrium, resulting in hydrate decomposition and hydrate saturation decline, which further cause reservoir damage. Previous works separated the study of hydrate saturation variation caused by thermal fluid injection and the reservoir damage caused by hydrate saturation variation. In this paper, a novel thermo-hydrologic-mechanical (THM) coupling model is proposed to simulate the thermal fluid injection in hydrate reservoir, and its effects on reservoir damage were analyzed. The results showed that thermal fluid injection causes the decomposition of hydrate, resulting in the decrease of hydrate saturation. The solid phase hydrates decompose into methane and water, which increases the pore pressure of hydrate reservoir and further affects the in-situ stress field. The change of effective stress induces pore deformation, and the hydrate decomposition also releases the space occupied by hydrate in reservoir pores, both affecting the reservoir permeability. Hydrate phase transition weakens the cementation of hydrate on rock particles and reduces the reservoir rock cohesion. In addition, the elastic modulus of hydrate decreases due to hydrate decomposition. The temperature and injection rate of thermal fluid are the main external factors affecting the hydrate phase transition. With the increase of thermal fluid temperature, hydrate saturation decreases due to hydrate decomposition, resulting in variation of reservoir parameters. Enhancing fluid injection rate can increase the reservoir pore pressure, which inhibits the hydrate decomposition. Highlights: A new thermo-hydrologic-mechanical (THM) coupling model is proposed. The dynamic property of reservoir caused by thermal fluid injection is considered. The mechanism of hydrate phase transition during thermal fluid injection is analyzed. Increasing injection rate and reducing fluid temperature can reduce reservoir damage.